Kilpailun rooli Suomen t & k-panostusten heikossa kehityksessä 2010-luvulla - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2021)
– The report's main objective is to assess the role that competition has played in the weak development of R&D investments in the Finnish corporate sector in the 2010s. The data suggest that the degree of competition relates to differences in Finland's industry-level R&D-intensity developments in the 2010s. Industries with declining R&D intensity were mainly concentrated, and the degree of competition in their markets weakened. In competitive industries, R&D intensity did not decrease, or it even increased. In these industries, profitability decreased mainly due to the decline in the profitability of continuing companies, but the impact of the structural change on profitability was positive. These findings reflect that competition was getting fiercer. Thus, the intensified competition in the 2010s increased companies' R&D investments or, at least, prevented them from shrinking in relation to the value-added produced. We further assessed the relationship between firms' returns to R&D and found that a decline in the R&D intensity of the Finnish business sector in the 2010s was not directly related to the returns to R&D investments.
Keywords: D22; L0; O3; O31; 330; R&D investments; Competition; Innovation policy